Utility of an interferon-gamma release assay as a potential diagnostic aid for active pulmonary tuberculosis - Lynn Taki-Eddin; Fawza Monem (Journal of Infection in Developing Countries)
Introduction: Sensitivity, specificity, early confirmation and obtaining an optimal specimen are challenging problems in active tuberculosis (TB) diagnosis. Interferon-gamma release assay (IGRA) is a good indicator for latent TB but can it be useful as a diagnostic tool for active TB? This study was designed to address these challenges and assess the potential of IGRA as a diagnostic indicator of active pulmonary TB by comparing it with other MT diagnostic conventional methods and molecular methods. Methodology: The study was conducted on 91 patients with suspicion of pulmonary active TB. QuantiFERON-TB-Gold In-Tube, a commercial IFN-gamma assay, was compared with Ziehl Neelsen (ZN) smear, Lowenstein Jensen's (LJ) egg-based culture, and real-time polymerase chain reaction. The final clinical diagnosis was the standard comparator of the study. Results: Active pulmonary TB was confirmed in 48/91 (52.7%) patients. Sensitivity, specificity, positive predicted value (PPV), and negative predicted value (NPV) were 72.9%, 100%, 100%, 76.78% for ZN smear, 77.1%, 97.67%, 97.36%, 79.24% for LJ culture, 89.9%, 67.4%, 75.4%, 85.3% for IGRA, and 66.6%, 95.3%, 94.1%, 71.9% for real-time PCR, respectively. Conclusion: Albeit confounding in the case of latent TB infected patients presenting with non-TB pulmonary disease, IGRA was more sensitive than the other conventional and molecular methods, so it may improve diagnostic accuracy when used in combination with other standard methods. High NPV of IGRA for the diagnosis of active TB proposed an additional role of this test to exclude the infection with active TB.